1998
DOI: 10.1080/15216549800201892
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of CD38/ADP‐ribosyl cyclase from rat lung

Abstract: SUMMARYPurification and characterization of CD38tADP-ribosyl cyctase in the rat lung tissue was performed with microsomes solubilized in Triton X-100 and the ADPribosyl cyclase was then purified using sequential column chromatography. Partially purified rat lung ADP-ribosyl cyclase was analyzed by immunoblotting using an antibody raised against a recombinant rat CD38 and showed the presence of monomer (42 kDa) and dimer (85 kDa) under non-reducing conditions but under reducing conditions, only the monomer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…For example, it has been suggested that two extracellular cysteines in CD38 (Cys119 and Cys201 in human CD38 or Cys123 and Cys205 in mouse CD38) could form interdisulfide bonds between CD38 monomers [22]. In agreement with this hypothesis, studies carried out with porcine heart, rat lung and rat hepatocytes showed that under nonreducing conditions CD38 forms dimers, while under reducing conditions CD38 is present in a monomeric form [23][24][25]. On the other hand, Umar et al have shown that CD38 oligomers, expressed by retinoic acid stimulated HL60 cells, are covalently stabilized by transglutaminase, suggesting an alternate biochemical mechanism for the stabilization of covalent CD38 oligomers [26].…”
supporting
confidence: 66%
“…For example, it has been suggested that two extracellular cysteines in CD38 (Cys119 and Cys201 in human CD38 or Cys123 and Cys205 in mouse CD38) could form interdisulfide bonds between CD38 monomers [22]. In agreement with this hypothesis, studies carried out with porcine heart, rat lung and rat hepatocytes showed that under nonreducing conditions CD38 forms dimers, while under reducing conditions CD38 is present in a monomeric form [23][24][25]. On the other hand, Umar et al have shown that CD38 oligomers, expressed by retinoic acid stimulated HL60 cells, are covalently stabilized by transglutaminase, suggesting an alternate biochemical mechanism for the stabilization of covalent CD38 oligomers [26].…”
supporting
confidence: 66%
“…Purification of CD38 from the Nuclear Fraction-The chromatography steps followed the method of Khoo and Chang (21,22). Briefly, the solubilized nuclear extract was subjected to a series of column chromatography, in the order of blue Sepharose CL-6B, hydroxyapatite, copper-iminodiacetic acid-agarose and concanavalin (Con) A-Sepharose columns.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies-Production and characterization of the polyclonal antibody against rat CD38 has been previously described (21,22). Various other antibodies were obtained from Affinity Bioreagents Inc. (Golden, CO), including monoclonal against type 1 (RyR-1) and type 2 ryanodine receptor (RyR-2) (clone 34-C), monoclonal anti-calnexin antibody (clone AF18), monoclonal anti-Na ϩ -K ϩ -ATPase antibody (clone 9A-5), polyclonal (rabbit) anti-calreticulin, and polyclonal (rabbit) anti-GRP78 (BiP) antibody.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations